The Effect of Polyethylene Terephthalate as an Additive on the Marshall Parameters of Asphalt Concrete Wearing Course (AC-WC) Mixtures at Ambient Temperature - Rhiza Afriady; Said Jalalul Akbar; Maizuar (Universitas Bengkulu, 2026)
Indonesia’s tropical climate, characterized by high temperatures and fluctuating humidity, presents a major challenge to the service life of pavements, as it accelerates asphalt aging and reduces the performance of the Asphalt Concrete–Wearing Course (AC-WC), the primary protective layer against traffic loads. This study investigates the effectiveness of Polyethylene Terephthalate (PET) waste as a modifying additive to enhance the resistance of AC-WC under ambient temperature conditions. Test specimens were prepared with 3% PET by asphalt weight and evaluated in accordance with Indonesian National Standards (SNI) and the 2018 Bina Marga General Specifications. The samples were exposed to temperatures of 23.77°C–31.11°C and an average humidity of 88.79% for periods of 0, 15, 30, 45, 60, 75, and 90 days, followed by stability, flow, and Marshall Quotient (MQ) testing. The results showed a stability increase of 13.74% at day 30, followed by a 16.81% decrease at day 90. Flow increased by an average of 19.70%, while MQ decreased by 15.75%. The mixture met the specification requirements for stability and MQ, but flow exceeded the limit after day 45. These findings confirm that PET can improve the early performance of AC-WC in tropical climates, although further optimization is required to control long-term plastic deformation. Keywords: Polyethylene terephthalate, AC-WC, Marshall parameters, ambient temperature, tropical climate.